Using Game Development to Teach Software Architecture. (6th May 2011) - Wang, Alf Inge; Wu, Bian
Abstract : This paper describes a case study of how a game project using the XNA Game Studio from Microsoft was implemented in a software architecture course. In this project, university students have to construct and design a type of software architecture, evaluate the architecture, implement an application based on the architecture, and test this implementation. In previous years, the domain of the software architecture project has been a robot controller for navigating a maze. Robot controller was chosen as the domain for the project, as there exist several papers and descriptions on reference architectures for managing mobile robots. This paper describes the changes we had to make to introduce an XNA game development project to the software architecture course, and our experiences from running a software architecture project focusing on game development and XNA. The experiences described in this paper are based on feedback from the course staff, the project reports of the students, and a mandatory course evaluation. The evaluation shows among other things that the majority of the students preferred the game project to the robot project, that XNA was considered to be suitable platform for a software architecture project, that the students found it useful to learn XNA and C#, and that some students were carried away when developing the game in the software architecture project.